Big data analytics capability as a mediator in the impact of open innovation on firm performance (2021)
ABSTRACT: Purpose: Big data analytics capability (BDAC) is the ability of a firm to capture and analyze big data toward the generation of insights. The literature has mainly focused on analyzing the direct effects of BDAC on different aspects related to firm performance such as finances and innovation. However, the lack of works analyzing the intermediation role BDAC could play is noticeable, particularly in organizational situations that pose great challenges in terms of data processing. Thus, the aim of this paper is to analyze BDAC mediation in the relationship between open innovation (OI), particularly customer involvement, and firm performance (financial and non-financial). Design/methodology/approach: Structural equation modeling was used to test the proposed model with survey data from a sample of 112 firms. Findings: The results show that BDAC has a partial mediating effect on the relationship between OI and financial performance, and between OI and non-financial performance. Nevertheless, this mediation is greater in the first relationship. Originality/value: The main contribution of the study is to offer a broader research perspective regarding the role of BDAC in the relationship between OI and firm performance. This study ultimately questions that research tradition in which this role has been reduced to that of a simple application of data analytics techniques. Instead, the results show BDAC is primarily an organizational skill that should be articulated with key processes, such as customer involvement, to maximize the financial and non-financial use of the large flow of data coming from the main OI activity of low and medium-technology companies.